Twenty-five Years of Global Takaful Trends: A Scopus Literature Exploration (2000-2025) - Syahnaz Sulaiman; Aidi Ahmi; Nur Salsabila Adam Malik; Asmak Ab Rahman (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by (Tier 2)